Atmosphere in the ward environment : a vulnerable dynamic phenomenon : a phenomenological study guided by the Vancouver School of Doing Phenomenology - Ragnheiður Alfreðsdóttir (2009)
Meistaraprófsritgerð við Royal College of Nursing Institute (London) og Háskólann á Akureyri, 2002. It has been pointed out that the atmosphere in the ward environment accounts for certain part of the variation in performance on individual wards. Emphases on economically driven health care have resulted in turmoil among hospital employees with obvious consequences. In the light of these circumstances the attention has been directed towards the infrastructure of hospitals, and the work environment is now under scrutiny as one of the important elements. However, its meaning for nurses has not received much attention. The aim of this study was to increase the understanding of ward environment with special emphasis on ward atmosphere and the meaning of empowering and disempowering atmosphere as nurses on inpatient wards experience it. A phenomenological study, guided by the Vancouver School of Doing Phenomenology, was conducted using individual and group dialogues with nurse managers and staff nurses. The dialogues were all together nineteen, nine with the head nurses and ten with the discussion groups. According to my understanding the ward atmosphere is a vulnerable dynamic phenomenon, which needs constantly to be attended to. The main theme of the phenomenon is relationships, and spans the range from a self-renewing empowering phenomenon, which is consciously motivated to a stagnated disempowering phenomenon with dead ends and no process. The essential structure of an empowering atmosphere is constructed of: open interaction, reciprocal care, holism. The essential structure of a disempowering atmosphere is constructed of: lack of caring, obstacles in the ward environment, a breach with the ward environment, bacbiting. The findings indicate that the ward atmosphere crystallises in the well-being, strength and confidence/lack of confidence of the individual/team. Moreover, that empowering ward atmosphere is the foundation for personal and professional development. Through deeper understanding of ward atmosphere, ...